2006
DOI: 10.1002/asi.20408
|View full text |Cite
|
Sign up to set email alerts
|

Web searching on the Vivisimo search engine

Abstract: The application of clustering to Web search engine technology is a novel approach that offers structure to the information deluge often faced by Web searchers. Clustering methods have been well studied in research labs; however, real user searching with clustering systems in operational Web environments is not well understood. This article reports on results from a transaction log analysis of Vivisimo.com, which is a Web meta-search engine that dynamically clusters users' search results. A transaction log anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 19 publications
1
32
1
3
Order By: Relevance
“…This is a problem quite extensively studied in the literature (e.g. [5,19]) and is also addressed by commercial systems such as Vivisimo [11]. 3 Most existing methods extract keywords from documents and calculate their similarity based on the keywords to obtain a set of clusters.…”
Section: Methods Of Evaluationmentioning
confidence: 99%
“…This is a problem quite extensively studied in the literature (e.g. [5,19]) and is also addressed by commercial systems such as Vivisimo [11]. 3 Most existing methods extract keywords from documents and calculate their similarity based on the keywords to obtain a set of clusters.…”
Section: Methods Of Evaluationmentioning
confidence: 99%
“…For example, Ozmutlu et al (2003) found that one tenth of Excite users and one third of AlltheWeb.com users conducted multiple-topic searches within a certain session. Koshman, Spink, and Jansen (2006) reported that 11.1% of search sessions over the Vivisimo search engine included a broad variety of search topics. Spink, Park, Jansen, and Pedersen (2006) found that a high degree of multiple topics exist in both two-query sessions (81%) and three or more query sessions (91%) on the AltaVista search engine.…”
Section: Multitaskingmentioning
confidence: 99%
“…For example, it has been observed that queries placed by users in the United States are likely to contain more operators (include, exclude, wildcard, etc.) than queries placed by users in Europe [53]. Furthermore, culture influences the perception that users develop about systems.…”
Section: Current Research In Computer Information Systems (Cis)mentioning
confidence: 99%